ANT1 overexpression models: Some similarities with facioscapulohumeral muscular dystrophy - Sandrine Arbogast; Heinrich Kotzur; Corinna Frank; Nathalie Compagnone; Thibault Sutra; Fabien Pillard; Sylvia Pietri; Nisrine Hmada; Daouda Moustapha Abba Moussa; Jamie Bride; Sarah Françonnet; Jacques Mercier; et al. (Redox Biology, 2022)
Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant disorder characterized by progressive muscle weakness. Adenine nucleotide translocator 1 (ANT1), the only 4q35 gene involved in mitochondrial function, is strongly expressed in FSHD skeletal muscle biopsies. However, its role in FSHD is unclear. In this study, we evaluated ANT1 overexpression effects in primary myoblasts from healthy controls and during Xenopus laevis organogenesis. We also compared ANT1 overexpression effects with the phenotype of FSHD muscle cells and biopsies.Here, we report that the ANT1 overexpression-induced phenotype presents some similarities with FSHD muscle cells and biopsies. ANT1-overexpressing muscle cells showed disorganized morphology, altered cytoskeletal arrangement, enhanced mitochondrial respiration/glycolysis, ROS production, oxidative stress, mitochondrial fragmentation and ultrastructure alteration, as observed in FSHD muscle cells. ANT1 overexpression in Xenopus laevis embryos affected skeletal muscle development, impaired skeletal muscle, altered mitochondrial ultrastructure and led to oxidative stress as observed in FSHD muscle biopsies. Moreover, ANT1 overexpression in X. laevis embryos affected heart structure and mitochondrial ultrastructure leading to cardiac arrhythmia, as described in some patients with FSHD.Overall our data suggest that ANT1 could contribute to mitochondria dysfunction and oxidative stress in FSHD muscle cells by modifying their bioenergetic profile associated with ROS production. Such interplay between energy metabolism and ROS production in FSHD will be of significant interest for future prospects.